To innovate the potential used of arc and oxy-acetylene welding to produce 3 dimensional form as an alternative to foundry work / Mohd Razif Mohd Rathi, Mursyidah Zainal Abidin and Zaidi Wasli - Mohd Rathi, Mohd Razif; Zainal Abidin, Mursyidah; Wasli, Zaidi (Research Management Institute (RMI), 2012)
This research is to innovate the potential used of Arc and Oxy-Acetylene welding tools and technique to produce three-dimensional forms as an alternative to foundry work. The Arc and Oxy-Acetylene tools commonly used by welder limited to jointing works. However, the researcher believes that the melting capabilities of the Arc and Oxy-Acetylene can be harnessed and be used to create other creative products. This research focus on fabricating three types of metal- copper, brass on mild steel structure to form layers of "surface skin" in replace of foundry work treatment (casting work). The advantage of this process is to offset or replace the expensive of foundry work. This process when applied to the production of creative work produces very rich tactile textures that complement the design. The flexibility of the process/ technique is easily adopted by experience welder and sculptor as such it will be an added value to their profession, to commercialize their product.